On the potential of 230Th, 231Pa, and 10Be for marine rain ratio determinations: A modeling study - Heinze, Christoph; Gehlen, M.; Land, C. (Global Biogeochemical Cycles, 2006)
The global distributions of the radionuclides 230Th, 231Pa, and 10Be are simulated with a biogeochemical ocean general circulation model. Sensitivity experiments for changes in the composition of the particle composition ratio (POC:CaCO3:BSi:clay, POC = particulate organic carbon, CaCO3 = calcium carbonate, BSi = biogenic silica) are carried out with and without biogeochemical feedback. The absolute water column concentrations of the radionuclides react significantly to changes in the particle rain composition. The radionuclide ratio in the sediment, however, is less sensitive to changes in the particle composition ratio. Still, selected areas could record composition ratio changes reliably for paleo reconstructions. Measurements of 230Th, 231Pa, and 10Be in the water column have the potential to monitor changes in the large scale CaCO3 production which may occur as a consequence of ocean acidification due to oceanic uptake of anthropogenic CO2.